2007
DOI: 10.1007/s00213-007-0936-3
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of sex and stress steroid hormones assessed daily over a 28-day cycle in early abstinent cocaine-dependent females

Abstract: Rationale-There is growing evidence of alterations in brain stress and reward circuits associated with cocaine dependence. Sex differences are also documented and sex steroid hormones have been linked to cocaine reinforcement.Objectives-The current study therefore assessed daily fluctuations in stress and sex hormones in cocaine-dependent females compared with healthy females.Method-Daily salivary samples of cortisol, progesterone, and estradiol were collected at waking across 28 days from 12 cocaine-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 77 publications
(86 reference statements)
5
44
0
Order By: Relevance
“…Similarly to Abplanalp et al (1979), however, they found a positive correlation between peak progesterone levels and measures of negative mood: crying and loneliness. Fox et al (2008) took daily measures of ovarian hormones using saliva samples, and weekly measures of mood using the POMS-bipolar form in healthy and cocaine addicted women. In the healthy women they found a negative correlation between negative mood and progesterone levels in the late luteal phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to Abplanalp et al (1979), however, they found a positive correlation between peak progesterone levels and measures of negative mood: crying and loneliness. Fox et al (2008) took daily measures of ovarian hormones using saliva samples, and weekly measures of mood using the POMS-bipolar form in healthy and cocaine addicted women. In the healthy women they found a negative correlation between negative mood and progesterone levels in the late luteal phase.…”
Section: Discussionmentioning
confidence: 99%
“…Often hormones or mood are only measured on a subset of days during the menstrual cycle (Abplanalp et al, 1979;Fox et al, 2008;Laessle et al, 1990;Rapkin et al, 2011;Stoddard et al, 2007). Composite measures of hormones, such as averages, may be used instead of directly assessing the relationship between daily hormone levels and daily mood (Stoddard et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These include childhood trauma and menstrual cycle phase, both of which are known to impact adrenergic (Pervanidou and Chrousos, 2007;Sinha et al, 2007a;Feltenstein et al, 2011) and HPA-axis function (Fox et al, 2008a;Carpenter et al, 2011). Inclusion of a non-stress and drug cue comparison imagery condition would also have provided a clearer understanding of the subtleties between biophysiological response to combined stress and cue compared with stress alone and cue alone.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the release of cortisol or estradiol was not affected by treatment with cinnamaldehyde (17). Recent reports suggest menstrual distress is related to higher estradiol levels, higher estradiol/progesterone ratios (18). Therefore, these actions of cinnamaldehyde may be attributed to the clinical effects of Cinnamon bark.…”
Section: Cinnamon Bark (Japanese Name: Keihi)mentioning
confidence: 93%